Paghimakas sa kinabuhi a history of the bolante trade in Southern Iloilo. - Gicana, Ma. Victoria V.
The study primarily looks into the early beginnings of the bolante trade and its devlopment in Southern Iloilo, its manner of operation and the changes that took place through time. Likewise, it will look into the contributing factors, which led to the growth and survival of the trade., In conducting this research, the researcher mainly utilized oral history using key informant method corroborated with secondary sources such published and unpublished materials. Photo-documentation was also employed . Bolante or bolantero/bolantera was corrupted from the Spanish word "ambular" or "ambulante", which means "to walk" or "walking". Its beginning was not known, but the idea of trading was already practiced since ancient times. Bolante basically refers to the kind of trade wherein a trader goes from one place to the other to sell their goods every market day. This kind of trade essentially evolved through time, due to some infrastructure developments. Primarily, bolante then refers to traders who just walk from one place to the other in selling in their goods; but now, bolante still refers to trader who transfer from on place to the other, however, the mode of going to other is through the use of vehicles. Basically these constant meetings of people was just carried out anywhere before; now it became institutionalized due to the presence of the market. Today, the word bolante has evolved and its defined as the set of relationship found at first in rural areas and later on extended to the urban areas. Bolante is a term long adapted in Hiligaynon due to its constant use to indicate vendors, who have small to large amount of goods from large capitalists on credit, which they paid after a period of time. When the loans have been paid, they are allowed to procure new supplies again. Today, the practice of bolante continues to grow and survive because of the presence of several factors: its economic significance, which guarantees answer to some financial needs of the family, the role of the capitalist enables the trader to continue his/her business in the midst of capital shortage, lastly the long involvement of the family in the business had left a legacy from generation to generation.